Single Versus Double Layer Anastomosis of Small Intestine. A Prospective Study at Lahore General Hospital Lahore, Pakistan (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To compare the outcome of single layer interrupted with conventional double layer small bowel anastomosis in terms of anastomotic leak, operative time and length of hospital stay.Patients and Methods: This prospective comparative study was conducted in Surgical Unit-II, Postgraduate Medical Institute at Lahore General Hospital, Lahore over a period of six months from December 2009 to June 2010. A total of 100 adult patients, requiring small bowel anastomosis were considered eligible for enrolment in  study. They were randomized to have either a single layer interrupted extra-mucosal anastomosis (Group A) or conventional double layer anastomosis (Group B). Anastomotic leak, time required to complete the anastomosis and hospital stay in both the groups were main outcome measures.Results: The mean age of patients in group A and B was 28.58±10.80 and 32.38±10.07 years respectively. Intestinal tuberculosis was the commonest disease requiring resection and anastomosis followed by the traumatic injuries of small intestine. Time required to complete the single layer anastomosis was significant less than double layer anastomosis group (P=0.0001). However there was no significant difference in the complications rate of both the groups (P=0.55). Hospital stay in single layer group was 6.74±0.83 days whereas it was 8±0.90 days in double layer group (P=0.0001).Conclusion: Single layer interrupted extra mucosal anastomosis is a better technique than double layer anastomosis, because it is associated with short operative time, better healing, comparable leakage rate and shorter hospital stay.
Keywords: Anastomosis, single layer anastomosis; double layer anastomosis, Leakage, Fistula, complications, small intestine